Efficient oxidation of arsenic in aqueous solution using zero valent iron- activated persulfate process. Issue 4 (August 2017) - Hussain, Imtyaz; Li, Mingyu; Zhang, Yongqing; Huang, Shaobin; Hayat, Waseem; Li, Yichun; Du, Xiaodong; Liu, Guoqiang
Graphical abstract: Abstract: The purpose of this study was to investigate the oxidation and removal of As(III) from aqueous solutions by persulfate (PS) activated with zero valent iron (ZVI). Batch experiments were performed to examine the effects of pH, ZVI dosage and PS concentration on the oxidation and removal of As(III). The oxidation efficiency of As(III) (50 μM) was 96% in the presence of persulfate (5 mM) and ZVI (0.3 g/L) within 30 min. As(III) oxidation and removal efficiency was significantly affected with initial pH and increased with decreasing pH. It has been observed that complete oxidation of As(III) is obtained at pH 3.0 within 10 min. The results showed that the oxidation efficiency increased with an increase in ZVI dosage from 0.1 to 0.3 g/L and an increase in PS concentration from 0.5 to 5.0 mM. But further increase in ZVI amount and PS would result in decrease the oxidation of As(III). Electron paramagnetic resonance (EPR) technique combined with two kinds of radical scavenging agents such as tert-butyl alcohol (TBA) and ethanol (EtOH) has been employed to confirm that sulfate radicals (SO4 − ) and hydroxyl radicals (OH) were generated from PS activation with ZVI for As(III) removal.